The different effects of four adenosine receptors in liver fibrosis - Yang, Lan; Gao, Zhao-wei; Wang, Xi; Wu, Xia-nan; Li, Si-min; Dong, Ke; Zhu, Xiao-ming (Frontiers in Pharmacology, 2024)
Background The adenosine–adenosine receptor pathway plays important roles in the immune system and inflammation. Four adenosine receptors (i.e., A1R, A2AR, A2BR, and A3R) have been identified. However, the roles of these receptors were different in the disease progress and even play opposite roles in the same disease. This study aims to investigate the roles of A1R/A2AR/A2BR/A3R activation in liver fibrosis. Methods Intraperitoneal injection of CCl4 into C57BL/6 mice was used to induce liver fibrosis in the models. Adenosine receptor agonists CCPA, CGS21680, BAY 60-6583, and namodenoson were used for A1R/A2AR/A2BR/A3R activation, respectively. Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels were used to evaluate the liver function. Hematoxylin and eosin (H&E) staining was used to investigate the pathological damage. Masson staining and Sirius Red staining were performed to evaluate the degree of collagen deposition. CCK8 and scratch assays were used to investigate the proliferation and migration ability of hepatic stellate cells (HSCs). Results By using liver fibrosis mouse models, we observed that the A1R and A2AR agonists aggravated liver fibrosis, characterized by increasing ALT and AST levels, more serious liver pathological damage, and collagen deposition. However, the A2BR and A3R agonists alleviated liver fibrosis. Moreover, the A1R and A2AR agonist treatment promotes the proliferation and migration of HSC line LX2, while A2BR and A3R agonist treatment inhibited LX2 proliferation and migration. Consistently, A1R and A2AR agonist treatment elevated the expression of α-SMA and Col1α1 in LX2, whereas A2BR and A3R agonist treatment inhibited the expression of α-SMA and Col1α1 in LX2 cells. Additionally, 5′-N-ethyl-carboxamidoadenosine (NECA), a metabolically stable adenosine analog, alleviated liver fibrosis and inhibited LX2 cell activity, proliferation, and migration. Conclusion This study demonstrated the different roles of A1R/A2AR/A2BR/A3R during liver fibrosis development via regulating the HSC activity and proliferation.